Analisis Strategi Bisnis Dengan Pendekatan Swot Pada Rumah Makan Dzaky Group - Aji Setiawan, Kurnia; Erlina, Rr; Firdaus, Luthfi (Shofanah Media Berkah, 2025)
This study aims to analyze the appropriate business strategy for Rumah Makan Dzaky Group in facing the culinary business competition in Bandar Lampung City. The research method used is a descriptive qualitative approach utilizing the SWOT analysis tool (Strengths, Weaknesses, Opportunities, Threats). Data were collected through observation, interviews, and documentation involving five respondents, consisting of one manager, two employees, and two customers of Rumah Makan Dzaky Group. The results of the study, based on the IE analysis, show that the strategic position of Rumah Makan Dzaky Group is in Quadrant V of the IE Matrix, which corresponds to the Hold and Maintain strategy. Strategies that can be implemented include market penetration through enhanced digital marketing, product development to meet consumer trends, and improving coordination and employee training to address internal weaknesses. Based on the SWOT analysis, thirteen strategic alternatives were identified, providing strategic direction for the company to enhance its competitiveness and maintain its presence amid the increasingly competitive culinary industry.